97.0k views
5 votes
Let f(x) = x2 + 3x − 4 and g(x) = x + 5. Find f(x) ⋅ g(x).

A) x3 + 3x2 + 16x − 20
B) x3 + 5x2 + 14x − 20
C) x3 + 8x2 + 11x − 20
D) x3 + 9x2 + 19x − 20

User Town
by
5.7k points

2 Answers

4 votes

Answer: [C]: " x³ + 8x² + 11x − 20 " .

______________________________________________________

Explanation:

______________________________________________________

Given: " f(x) = x² + 3x − 4 " ; and

" g(x) = x + 5 " ;

Find: " f(x) ⋅ g(x) " :

______________________________________________________

f(x) ⋅ g(x) =

" (x² + 3x − 4) (x + 5) " ;

" (x + 5) (x² + 3x − 4) " ;

______________________________________________________

Note: " (a + b) (c + d + e) = ac + ad + ae + bc + bd + ae " ;

______________________________________________________

→ " (x + 5) (x² + 3x − 4)

= (x * x²) + (x * 3x) + (x*-4) + (5*x²) + (5*3x) + (5*-4) " ;

= (x³) + (3x²) + (-4x) + (5x²) + (15x) + (-20) ;

= x³ + 3x² − 4x + 5x² + 15x − 20 ;

→ Combine the "like terms" :

+ 3x² + 5x² = + 8x² ;

− 4x + 15x = + 11 x ;

______________________________________________________

→ And rewrite:

______________________________________________________

→ " x³ + 8x² + 11x − 20 " ;

______________________________________________________

→ which is: Answer choice: [C]: " x³ + 8x² + 11x − 20 " .

______________________________________________________

Hope this helps!

Best wishes!

______________________________________________________

User Bshanks
by
5.2k points
4 votes

Answer:


x^3 + 8x^2 + 11x-20

Explanation:

f(x) = x^2 + 3x − 4

g(x) = x + 5

To find f(x) * g(x) we multiply f(x) with g(x)


f(x) * g(x) = (x^2 + 3x -4) * (x+5)

First multiply each term in f(x) and multiply with x+5

x^2 times x+5 becomes
x^3+5x^2

3x times x+5 becomes
3x^2 + 15x

-4 times x+ 5 becomes -4x -20

so f(x) * g(x) =
x^3 + 5x^2 +3x^2 + 15x -4x -20

Combine like terms

f(x) * g(x) =
x^3 + 8x^2 + 11x-20

User Yinjia
by
5.9k points